The Influence of Leadership, Communication and Collaboration on the Performance of Members of the New Indonesian Generation (Genbi) Solo Utp Surakarta Commissariat - Paulina Ria Vanesa; Tia Febriana; Zandra Dwanita Widodo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine the influence of communication, teamwork and leadership on the work of GenBI Solo employees, UTP Surakarta Commissariat, both directly and indirectly. This research is a quantitative analysis and the respondents of this research are members of the GenBI Solo UTP Surakarta Commissariat with a total of 33 samples from a population of 50. The sample used in this research is a non-probability sampling technique which involves selecting a voluntary sample of respondents. This type of research uses descriptive quantitative analysis with data collection techniques using interviews and questionnaires conducted with participants. The results of this research show that the indicators of the influence of leadership, communication, and cooperation greatly influence the performance of GenBI Solo Members, UTP Surakarta Commissariat.